Protective effect of interferon-alpha on carbon tetrachloride-induced nephrotoxicity. - Dogukan, Ayhan; Akpolat, Nusret; Celiker, Huseyin; Ilhan, Nevin; Halil Bahçecioglu, Ibrahim; Günal, Ali Ihsan (My University, 2003)
BACKGROUND: The aim of this study was to investigate the effect of chronic administration of interferon-alpha 2b for the prevention of carbon tetrachloride (CCl4)-induced oxidative stress and nephrotoxicity. METHODS: Thirty rats were divided into three groups: control, CCl4+placebo (CCl4+P) and CCl4+interferon-alpha 2b (CCl4+INF). Control rats were treated with pure olive oil. The other rats were treated for seven weeks with subcutaneous injections of CCl4 (0.15 mL /kg) in pure olive oil three times a week. Rats were killed at the end of the seventh week and renal histopathological examinations were done: specimens of renal tissue were obtained for investigating oxidative stress parameters, including malondialdehyde (MDA) and glutathione peroxidase (GSH-Px). RESULTS: Tubular changes, glomerular hypercellularity, and capillary obliteration were significantly less in the CCl4+INF group than with CCl4+P (p<0.05) and the interstitial fibrosis score for the CCl4+INF group was similar to the control group. However, the interstitial inflammation score was higher in the CCl4+INF group than the control group (p<0.05). No change was observed in the CCl4+P group. Renal MDA levels in the control and CCl4+INF groups were significantly lower than the CCl4+P group, while GSH-Px was significantly higher (p<0.001). There was no difference between the control and CCl4+INF groups in oxidative stress markers (p>0.05). CONCLUSIONS: Administration of interferon-alpha 2b to CCl4-treated rats prevented interstitial fibrosis, probably as a result of its antifibrogenic effect. It also reduced intrarenal oxidative stress in rats with CCl4-induced nephrotoxicity.
Keywords: Analysis of Variance; Animals; Carbon Tetrachloride; Disease Models, Animal; Glutathione Peroxidase; Immunohistochemistry; Injections, Subcutaneous; Interferon Alfa-2b; Kidney; Kidney Diseases; Male; Malondialdehyde; Oxidative Stress; Probability; Protective Agents; Random Allocation; Rats; Rats, Wistar; Reference Values; Sensitivity and Specificity; alpha2b interferon; carbon tetrachloride; glutathione peroxidase; malonaldehyde; protective agent; analysis of variance; animal; article; comparative study; disease model; drug effect; immunohistochemistry; kidney; kidney disease; male; oxidative stress; pathology; probability; randomization; rat; reference value; sensitivity and specificity; subcutaneous drug administration; Wistar rat